Victim Pays Damages to Tortfeasor: The When and Wherefore - Shmueli, Benjamin; Sinai, Yuval (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
Is there a reality in which the victim pays damages to the tortfeasor? This article analyzes Calabresi and Melamed’s liability rule for the damaging party (Rule 4), where the damaged party has the right to prevent pollution if the polluter is compensated first. Under the conventional application of this rule, the victim first collects the money and compensates the injurer, and only then is the injurer required to eliminate the nuisance (ex ante). There is no reference to a possibility of the injurer first eliminating the nuisance and only then receiving compensation (ex post). We argue that the timing of the payment should be changed when the activity causing the nuisance has social and economic value. Each version of the rule advances the aggregate welfare in some sense, but also harms it in another.The primary aim of the present article is to introduce a new model for Rule 4 that would guide legislators, regulators, and judges in deciding when to order compensation as a condition for eliminating the nuisance and when to order the injurer to remove the nuisance first and only then collect the funds.This article also introduces a comparative perspective that reveals the potential use of the ex post version of Rule 4, as manifest in sources of the Jewish legal tradition. This comparison further bolsters our proposal in favour of a division between ex ante and ex post versions of the rule.Ultimately, offering two versions for the implementation of Rule 4 would better enable the adaptation of a suitable solution according to the circumstances and thus would widen the possibilities for the rule’s use.